Multi-attribute grey target decision method with three-parameter interval grey number. Issue 2 (1st August 2016) - Li, Ye; Zhu, Shanli; Guo, San-dang
Abstract : Purpose: – The purpose of this paper is to propose the grey target decision method based on three-parameter interval grey number for dealing with multi-attribute decision-making problems under uncertain environment. Design/methodology/approach: – First, the kernel and ranking method of three-parameter interval grey number are defined, which is the basis of determining the positive and negative bull's-eye. Next, a new distance measure of three-parameter interval grey number is defined in view of the importance of the "center of gravity" point. Furthermore, a new comprehensive bull's-eye distance is proposed based on the kernel which integrates the distance between different attributes to the positive and negative bull's-eye. Then attribute weights are obtained by comprehensive bull's-eye distance minimum and grey entropy maximization. Findings: – The paper provides a grey target decision method based on three-parameter interval grey number and example analysis shows that the method proposed in this paper is more reasonable and effective. Research limitations/implications: – If we have a better understanding of the distribution characteristics of three-parameter interval grey number, it is possible to have a more reasonable measure of the distance of three-parameter interval grey number. Practical implications: – The paper provides a grey target decision method, which can help decision maker deal with multi-attribute decision-making problems under uncertain environment. Originality/value: – This paper proposed the kernel and ranking method of three-parameter interval grey number, and defined a new distance measure of three-parameter interval grey number and proposed a new comprehensive bull's-eye distance, Furthermore, this paper structured a grey target decision method based on three-parameter interval grey number.